Inclusive Education Teaching Practices and Use of Digital Storytelling among Non-Sped Teachers in Public High School (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study explored the use of digital storytelling (DST) as an instructional tool for inclusive teaching among non-SPED teachers at Zapatera National High School in Cebu City, Cebu. It aimed to determine the extent of DST tool utilization, identify inclusive teaching strategies employed by teachers, assess the perceived effectiveness of DST in enhancing learning outcomes, and examine the challenges and support needs associated with its implementation. The study employed a quantitative, descriptive-correlational research design, with data collected from 20 non-SPED teachers using a validated, researcher-made questionnaire. Results indicated that teachers perceived digital storytelling as highly effective in improving student engagement, comprehension, attention, creativity, and digital literacy. Despite these positive perceptions, the actual use of DST tools was limited. Teachers primarily utilized commonly accessible platforms, such as PowerPoint, Canva, and Google Slides, while many other digital storytelling tools were rarely or never employed. This limited utilization was attributed to several challenges, including time constraints, insufficient ICT resources, lack of technical skills, and inadequate administrative support. The results showed that teachers consistently practiced inclusive teaching by using visual aids, creating supportive classroom environments, and giving clear instructions to learners. Although the use of digital storytelling tools alone was not directly linked to improved learning outcomes, the study found a moderate relationship between inclusive teaching practices and the effectiveness of digital storytelling. This indicates that digital storytelling is most effective when it is thoughtfully integrated with inclusive strategies in lesson planning and classroom instruction.